(untitled) (Research, Society and Development, 2021)
Pemphigus Vulgaris is a chronic autoimmune disease characterized by the formation of blisters on the skin and mucous membranes, which results in the loss of adhesion between keratinocytes, causing the disintegration of cells, a phenomenon called acantholysis. In addition to immunoglobulin G (IgG) antibodies directed against desmosomal proteins. Among immunological mediated dermatological pathologies, pemphigus vulgaris is the most common disease among pemphigus types, becoming aggressive when not previously diagnosed, initially presenting its manifestations in the oral cavity, thus the Dental Surgeon plays a crucial role in the diagnosis and management clinical presentation of oral manifestations. The case reported in this article is configured as a condition of pemphigus vulgaris that was treated and followed up, in parallel with medical treatment, at the basic health unit in the municipality of Belém-PB. However, it is concluded that it is important for the dentist to have knowledge for the recognition of autoimmune diseases, specifically pemphigus vulgaris, since early diagnosis is essential for the treatment of the pathology, avoiding posterior systemic disorders. In addition to emphasizing the role of the dental approach and the importance of multiprofessional performance.